An Evidence-Based Perspective on The 2020 Royal Australian and New Zealand College of Psychiatrists Clinical Practice Guidelines. (August 2022) - Malhi, Gin S; Bell, Erica; Bassett, Darryl; Boyce, Philip; Bryant, Richard; Hazell, Philip; Hopwood, Malcolm; Lyndon, Bill; Mulder, Roger; Porter, Richard; Singh, Ajeet B; Murray, Greg
Objective: To rebut the claims made in an opinion piece by Anaf and colleagues regarding the recommendations for psychotherapy within the 2020 RANZCP Mood Disorders Clinical Practice Guidelines (CPG). Conclusions: The CPG attaches importance to psychological interventions and recommends their administration as first-line in the treatment of depression. The concerns raised by Anaf and colleagues have no basis and are readily dismissed by referring to the guidelines. Therefore, we strongly encourage clinicians to formulate their own views by reading the guidelines for themselves.